The Effects of Nitrogen Addition on the Uptake and Allocation of Macro- and Micronutrients in Bothriochloa ischaemum on Loess Plateau in China - Ai, Zemin; Wang, Guoliang; Liang, Chutao; Liu, Hongfei; Zhang, Jiaoyang; Xue, Sha; Liu, Guobin (Frontiers in Plant Science, 2017)
The effects of nitrogen (N) addition on the macro- and micronutrient concentrations, storage, and allocation of Bothriochloa ischaemum (L.) Keng, a native forage plant on the Loess Plateau in China remain unclear. We studied the effects of N addition at 0 (CK), 2.5 (N1), 5.0 (N2), and 10.0 (N3) g N m−2 y−1. N addition significantly decreased the available copper (Cu), zinc (Zn), and total Cu concentration, but significantly increased the available iron concentration in the soil. Cu, manganese (Mn), and sodium (Na) concentrations in aboveground tissues and potassium (K), magnesium, and Zn concentrations in belowground tissues significantly increased with N addition. Calcium (Ca) concentrations in belowground tissues decreased significantly. The ratios of above- to belowground Ca, Cu, Zn, and Mn significantly increased with N addition. The maximum ratios appeared at N2 for Cu, Zn, and Mn. The aboveground, belowground, and total biomass storage of studied nutrients significantly changed with N addition, and most attained maximum values under N2 treatment. The storage ratios of above- to belowground Cu, Zn, Mn, and Na attained maximum values at N2. We conclude that N addition significantly, but differentially influence the macro- and micronutrient concentrations and storage in B. ischaemum. B. ischaemum allocated and accumulated increased macro- and micronutrients to its aboveground tissues and exhibited high total storage when the amount of N addition reached 5 g N m−2 y−1.